Uncovering Diversity within the Glomeromycota: Novel Clades, Family Distributions, and Land Use Sensitivity - Camille S. Delavaux; Alexis Aellen; Sidney L. Stürmer; Silmar Primieri; Ursel M. E. Schütte; Devin M. Drown; Robert J. Ramos; Thomas W. Crowther; James D. Bever (Ecology and Evolution)
ABSTRACT Arbuscular mycorrhizal fungi (AMF, phylum Glomeromycota) are essential to plant community diversity and ecosystem functioning. However, increasing human land use represents a major threat to native AMF globally. Characterizing the loss of AMF diversity remains challenging because many taxa are undescribed, resulting in poor documentation of their biogeography and family‐level disturbance sensitivity. We survey sites representing native and human‐altered ecosystems across the American continents—in Alaska, Kansas, and Brazil—to shed light on these gaps. Using a recently developed pipeline for phylogenetic placement of eDNA, we find evidence for three putative novel clades within the Glomeromycota, sister to Entrophosporaceae, Glomeraceae, and Archaeosporaceae, with evidence for geographic structuring. We further find that taxa in the Diversisporaceae, Glomeraceae, and Entrophosporaceae relatively high families are overrepresented and more diverse in temperate samples. By contrast, the diversity of taxa that cannot be placed into a family is higher in tropical samples, suggesting that tropical sites harbor relatively high undescribed AMF diversity. Moreover, we find evidence that Entrophosporaceae is more tolerant, while Glomeraceae is more sensitive to disturbance. These results underscore the vast undescribed diversity of AMF while highlighting a way forward to systematically improve our understanding of AMF biogeography and response to human disturbance.